DATA QUALITY IN BI SYSTEMS FROM MANAGEMENT ACCOUNTING PERSPECTIVE - Siltala, Akseli (My University, 2023)
The role of management accounting has significantly changed during the last couple of decades. The role has become more complex, and controllers have adopted new IT systems. Business in telligence (BI) solutions have become one of the main information sources for management ac counting. Controllers always need to validate the data, and what they are using in forecasts and analyses. Business intelligence solutions have differences in the aspects of data quality compared to other information sources. This research aims to increase understanding of the data quality in BI applications, as there is limited academic research in this field. The role of management ac counting in BI data quality assurance is mostly unresearched. This research increases understand ing of the practices controllers utilize to ensure high data quality in BI solutions and about the roles of other company functions in relation to BI data quality assurance. This thesis is conducted as qualitative research by using an action-oriented approach, which ena bles a profound understanding of the subject to be formed. The empirical research consisted of six semi-structured interviews in three large Finnish companies. Most of the data quality issues in BI applications originate from human errors in the data input process. Another source for data quality discrepancies is issues in the data transfer and load pro cesses. There is an especially high probability for data quality issues when source systems are updated and changed. The responsibility to ensure high data quality in BI is divided between the business side, data analysts, and controllers. Data analysts are responsible for the BI databases. Based on the empirical results, external service providers can be used to maintain and create such databases. The role of management accounting is to verify the BI data by using reconciliations and trend analyses. Controllers also have an important role in BI data quality development pro jects, which are used as long-term solutions to improve BI data quality. Depending on the organ izational structure controllers are either leading the process to achieve high data quality in BI applications or they at least have a highly important role in the process. The improvement projects are especially important for the controllers because they are often using a lot of time to ensure the correctness of the data. Therefore, a detailed understanding of the dataflows between different IT systems and developed IT skills are required from modern management accountants to ensure high data quality in BI systems. The management of BI data quality follows the traditional risk management process. However, the approach is different in BI data quality management as discrepancies are not tolerated. This affects the risk categorization process as all the risks are deemed severe and therefore require action. Based on the empirical evidence, companies often lack an organization-wide plan to man age data quality in BI applications. The continuous mitigation planning for data quality risks is essential because it creates the framework to achieve high information quality in BI applications and to secure the continuity of data quality management. If a company is missing a plan for data quality management, there is a risk that the quality controls are performed as a one-time action point. The existence of a plan also clarifies the roles and responsibilities between different com pany functions, thereby eliminating possible communication issues relating to the management of BI data quality.

Johdon laskentatoimen rooli on muuttunut merkittävästi viimeisten vuosikymmenien aikana. Roolista on tullut monipuolisempi ja controllerit ovat ottaneet käyttöön uusia tietojärjestelmiä. Business intelligence (BI) -järjestelmistä on tullut keskeinen tietolähde johdon laskentatoimelle. Controllereiden tulee aina varmistaa käyttämänsä tiedon oikeellisuus, jota he hyödyntävät liike toimintaa koskevissa ennusteissa ja analyyseissa. BI-ratkaisuissa on tiedon oikeellisuutta koskien erovaisuuksia verrattuna muihin johdon laskentatoimen hyödyntämiin tietolähteisiin. Tämän tut kimuksen tavoitteena on lisätä ymmärrystä datan laadunhallinnasta BI-järjestelmissä. Akateemi sessa kirjallisuudessa johdon laskentatoimen roolia BI-datan laadunvarmistuksessa on tutkittu hy vin rajallisesti. Tämä tutkimus lisää ymmärrystä controllereiden käyttämistä menetelmistä BI datan laadunvarmistamisessa, sekä muiden yrityksen sidosryhmien roolista tässä prosessissa. Tämä tutkimus on toteutettu laadullisena tutkimuksena, hyödyntäen toiminta-analyyttistä lähes tymistapaa, mikä mahdollistaa syvällisen ymmärryksen muodostamisen tutkittavasta aiheesta. Empiirinen aineisto koostuu kuudesta puolistrukturoidusta haastattelusta, jotka on tehty, kol messa suuressa suomalaisessa yrityksessä. Suurin osa BI-järjestymien datan laatuun liittyvistä ongelmista johtuu inhimillisistä virheistä da tansyöttöprosessissa ja toinen virheiden päälähde on ongelmat datansiirto ja -latausvaiheissa. Riski datan virheiden syntymiselle korostuu erityisesti tilanteissa, joissa tehdään muutoksia yri tyksen IT-järjestelmiin. Vastuu BI-datan oikeellisuudesta jakautuu liiketoiminnan, johdon lasken tatoimen ja data-analyytikkojen välille. Data-analyytikot ovat vastuussa tietokantojen toiminnasta ja kehittämisestä. Empiiristen tulosten pohjalta myös ulkoista palveluntarjoajaa voidaan hyödyn tää kyseisissä tehtävissä. Johdon laskentatoimen rooli on varmistaa tiedon oikeellisuus täsmäy tyksillä ja analyyseilla. Controllereille on myös tärkeä rooli datan laadun kehittämisessä. Kehi tysprojektit toimivat pitkäaikaisena ratkaisuna datan laadun ongelmiin ja niiden avulla voidaan vähentää controllereiden datan laadunvalvontaan käyttämää aikaa. Johdon laskentatoimen rooli kehitysprojekteissa datan laadun osalta riippuu organisaatiorakenteesta. Controllerit ovat joko johtamassa kyseisiä projekteja tai heillä on ainakin merkittävä rooli näissä projekteissa. Tämän vuoksi moderneilta johdon laskentatoimen ammattilaisilta vaaditaan ymmärrystä tiedon liikku misesta yrityksen eri tietojärjestelmien välillä sekä erinomaisia IT-taitoja, jotta he pystyvät var mistamaan tuottamansa tiedon oikeellisuuden. BI-datan laadunhallinta noudattaa pitkälti perinteistä riskienhallintaprosessia, mutta tärkeimpänä erona on lähestymistapa, jossa ei sallita toleransseja poikkeamille datan laadussa. Tämä vaikuttaa riskienluokitteluprosessiin, koska kaikki riskit nähdään vakavina ja toimenpiteitä vaativina. Em piiristen tulosten perusteella yrityksiltä puutuu usein koko organisaation kattava suunnitelma BI datan laadun varmistamiseen. Suunnitelman ylläpitäminen ja päivittäminen ovat erityisen tär keitä, sillä ne luovat viitekehyksen korkean datan laadun saavuttamiseksi ja viitekehys varmistaa datan laatuun liittyvän riskienhallinnan jatkuvuuden. Suunnitelman puuttuminen tai päivittämättä jättäminen luo riskin, jolloin datan laatuun liittyvät kehitysprojektit jäävät yksittäisiksi toimenpi teiksi ilman jatkoseurantaa. Datan laadunhallinnan suunnitelmallisuus myös edistää selkeää roo lijakoa yrityksen eri sidosryhmien välillä ja se eliminoi mahdolliset kommunikaatio-ongelmat liittyen BI-datan laatuun.
Keywords: Business Intelligence, data quality, controller